2003
DOI: 10.1093/jnci/djg105
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Incidence in Patients With Type 1 Diabetes Mellitus: A Population-Based Cohort Study in Sweden

Abstract: Although patients with type 2 diabetes have elevated risks of liver, pancreatic, kidney, and endometrial cancer, little is known about the risk of cancer for patients with type 1 diabetes. We conducted a cohort study to examine cancer incidence among 29 187 patients in Sweden who were hospitalized for type 1 diabetes from 1965 through 1999. Relative risks of cancer were estimated by age-, sex- and calendar year of follow-up--adjusted standardized incidence ratios (SIRs), using data for the entire Swedish popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
198
4
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(218 citation statements)
references
References 21 publications
13
198
4
3
Order By: Relevance
“…Of these 25 studies, five were cohort studies that used incidence and/or mortality rate ratios as the measure of RR [9,21,[24][25][26] (Table 1), 13 were case-control studies [10-20, 22, 23] (Table 2) and seven were cohort studies that used standardised incidence and/or mortality ratio as the measure of risk [34][35][36][37][38][39][40] (Table 3). Twelve studies were conducted in the USA, ten in Europe, one in South America and one in Asia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these 25 studies, five were cohort studies that used incidence and/or mortality rate ratios as the measure of RR [9,21,[24][25][26] (Table 1), 13 were case-control studies [10-20, 22, 23] (Table 2) and seven were cohort studies that used standardised incidence and/or mortality ratio as the measure of risk [34][35][36][37][38][39][40] (Table 3). Twelve studies were conducted in the USA, ten in Europe, one in South America and one in Asia.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies reported on type 1 diabetes and endometrial cancer, one case-control study [11], two studies providing standardised incidence ratio [34,35] and one study Measure of relative risk is an odds ratio except for one (Maatela, 1994 [15]). …”
Section: Resultsmentioning
confidence: 99%
“…The baseline risk of cancer is much lower in this age group, together with the likelihood of pre-existing cancer foci. Furthermore, a proportion had type 1 diabetes, which is associated with a different range of cancers [5]. Statistical adjustment cannot fully compensate for biological differences between groups.…”
Section: What Does It All Mean?mentioning
confidence: 99%
“…The excess risk for each cancer is~30% (colon),~50% (pancreas) and~20% (breast) [2][3][4]. Type 1 diabetes carries an excess cancer risk of~20%, but involves a different range of tumours [5]. The major cancers linked with type 2 diabetes are also associated with obesity or insulin resistance, suggesting that factors other than glucose play an important role [6].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with either type 1 or type 2 diabetes mellitus were included although the type and the frequency of malignancies associated with either disease are very different [7]. Patients with type 1 diabetes cannot sufficiently be treated with insulin glargine only.…”
mentioning
confidence: 99%